An unorthodox approach by an orthodox bioethicist: H. Tristram Engelhardt, Jr. and transplants - Ladas, Ioannis (Bioethica, 2023)
The problem of organ shortage is constantly increasing, and along with it, discussions in favor of various forms of controlled compensation/reward for organ procurement are also growing. Although the practice of "organ donation" in exchange for compensation is legally prohibited in our days, it has passionate supporters, including H. T. Engelhardt, Jr., who happens to be the only Christian orthodox bioethicist advocating that there is no ethical barrier to accepting or even requesting payment for organ donation. Within this context, this article deals with the concept of compensation in organ donation and examines the approach of the Texan bioethicist. It should be noted that Engelhardt's position represents a personal opinion, which is positively evaluated only within the realm of healthy dialogue, while simultaneously highlighting the need for vigilance in maintaining a constant ideological awareness that will create insurmountable barriers stronger than laws protecting against the commodification of organs.